Biodegradable and Biocompatible Poly(Ethylene Glycol)‐based Hydrogel Films for the Regeneration of Corneal Endothelium. Issue 9 (20th March 2014) - Ozcelik, Berkay; Brown, Karl D.; Blencowe, Anton; Ladewig, Katharina; Stevens, Geoffrey W.; Scheerlinck, Jean‐Pierre Y.; Abberton, Keren; Daniell, Mark; Qiao, Greg G.
<x xml:space="preserve">Abstract</x> Corneal endothelial cells (CECs) are responsible for maintaining the transparency of the human cornea. Loss of CECs results in blindness, requiring corneal transplantation. In this study, fabrication of biocompatible and biodegradable poly(ethylene glycol) (PEG)‐based hydrogel films (PHFs) for the regeneration and transplantation of CECs is described. The 50‐μm thin hydrogel films have similar or greater tensile strengths to human corneal tissue. Light transmission studies reveal that the films are >98% optically transparent, while in vitro degradation studies demonstrate their biodegradation characteristics. Cell culture studies demonstrate the regeneration of sheep corneal endothelium on the PHFs. Although sheep CECs do not regenerate in vivo, these cells proliferate on the films with natural morphology and become 100% confluent within 7 d. Implantation of the PHFs into live sheep corneas demonstrates the robustness of the films for surgical purposes. Regular slit lamp examinations and histology of the cornea after 28 d following surgery reveal minimal inflammatory responses and no toxicity, indicating that the films are benign. The results of this study suggest that PHFs are excellent candidates as platforms for the regeneration and transplantation of CECs as a result of their favorable biocompatibility, degradability, mechanical, and optical properties.